An Analytical Study of Using English Pronunciation Applications to Improve Student’s Pronunciation - Abraheem, Abdalqadir (Journal of English Language Teaching and Applied Linguistics, 2025)
In the current day, which is marked by the widespread integration of technology in education, good communication is vital, and the English language has evolved to be the common language that brings together people from many backgrounds. One’s ability to pronounce words correctly—a fundamental component of language competence—directly correlates with effective communication. The aim of this study is to look at the possible consequences of including a creative pronunciation application in students’ educational process. Using a quantitative approach and gathering information using a structured questionnaire procedure. The aim of this paper is to assess the practical consequences of adopting an English Pronunciation Application as a supportive medium in the process of enhancing students’s pronunciation skills as well as their efficacy. The results suggest that the English Pronunciation Application has been successful in its function as a supporting tool, which has led to a notable development in the pronunciation skills of students.